2023
DOI: 10.3390/jcm12030738
|View full text |Cite
|
Sign up to set email alerts
|

Current Advances in Gene Therapies of Genetic Auditory Neuropathy Spectrum Disorder

Abstract: Auditory neuropathy spectrum disorder (ANSD) refers to a range of hearing impairments characterized by an impaired transmission of sound from the cochlea to the brain. This defect can be due to a lesion or defect in the inner hair cell (IHC), IHC ribbon synapse (e.g., pre-synaptic release of glutamate), postsynaptic terminals of the spiral ganglion neurons, or demyelination and axonal loss within the auditory nerve. To date, the only clinical treatment options for ANSD are hearing aids and cochlear implantatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 138 publications
0
5
0
Order By: Relevance
“…However, the real prevalence of hearing impairments associated with DOA might be higher than reported due to the high variability in disease manifestation and progression [ 58 ] as well as the heterogeneity of the clinical profiles of auditory neuropathy [ 59 ]. In this respect, it was reported that 25% of patients harboring mitochondrial DNA mutations responsible for Leber’s hereditary optic neuropathy, previously considered as having normal hearing, had electrophysiological evidence of auditory neuropathy [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the real prevalence of hearing impairments associated with DOA might be higher than reported due to the high variability in disease manifestation and progression [ 58 ] as well as the heterogeneity of the clinical profiles of auditory neuropathy [ 59 ]. In this respect, it was reported that 25% of patients harboring mitochondrial DNA mutations responsible for Leber’s hereditary optic neuropathy, previously considered as having normal hearing, had electrophysiological evidence of auditory neuropathy [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…These hidden auditory neuropathies are undiagnosed by classic, current clinical audiological tests such as audiogram. In animal models, hidden auditory neuropathy can be caused by moderate noise exposure-, aging-, or genetic factors-inducing a loss of IHC synapses, auditory nerve terminals, and cochlear Schwann cells [ 59 , 61 , 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…MRI testing reviled that the electrophysiological picture of congenital ANSD might be also due to the hypoplastic cochlear nerve (cochlear nerve deficiency). ANSD might be also acquired letter in life as a result of late-onset genetic-based mechanisms or due to an autoimmune reaction [3][4][5][6].…”
Section: Etiology Of Auditory Neuropathy Spectrum Disordermentioning
confidence: 99%
“…It is a very promising procedure for the future. Specially for the field of neurodegeneration of auditory pathways [84].…”
Section: Author Detailsmentioning
confidence: 99%